(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of single dose oral dexamethasone versus multi-dose prednisolone in the treatment of acute asthma exacerbation. Study Design: Randomized controlled trial Study. Place and Duration of Study: This study was conducted at the Department of pediatrics, Gomal Medical College D.I Khan from Sep 2015 to March 2016. Materials and Methods: A total of 160 children under 12 years of age were divided in 2 groups at random, dexamethasone was given to children in A group and in group B prednisolone was given. All children were followed until 10th day after discharge to determine the efficacy of treatment in terms of relapse. Results: Group A contained children having mean age 7.53 + 2.23 years & group B had children with mean age 8.1 + 2.3 years (p value 0.107). Of the whole sample, we had 65% males in group A and 55% in group B, female gender was found in 25% in group A while 45% in group B. (p 0.197). Efficacy in terms of relapse for group A was 85% while that of group B was 70%, (p value of 0.023). Conclusion: The oral dexamethasone is more effective than oral prednisolone in the treatment of acute exacerbation of bronchial asthma in children below 12 years, however, we recommend more randomized controlled trials specially in various combinations with bronchodilators for the generation of solid evidence in the treatment of acute asthma.